1, 8-Naphthalimides 3-substituted with imine or β-ketoenamine unit evaluated as compounds for organic electronics and cell imaging. (September 2021) - Korzec, Mateusz; Kotowicz, Sonia; Gawecki, Robert; Malarz, Katarzyna; Mrozek-Wilczkiewicz, Anna; Siwy, Mariola; Schab-Balcerzak, Ewa; Grzelak, Justyna; Maćkowski, Sebastian
Abstract: In this paper, we describe both new as well as described in our previous works 1, 8-naphthalimide derivatives substituted at the 3-C position with imine or β-ketoenamine unit in order to demonstrate a broader scope of research enabling of analysis between the structure-properties relationship relevant to the application of these compounds in organic electronics and cellular imaging. Thermal, physicochemical, optical, electrochemical, electroluminescence, and biological properties of a series of derivatives containing the 1, 8-naphthalimide unit were tested and compared. This allowed the determination of the impact of substituents in the imide part (hexylamine, phenylethyl, benzyl, fluorobenzyl, methylbenzyl), type of bond (imine or ketoenamine) as well as the substituent on the naphthalene ring (2-hydroxyphenyl, 5-bromo-2-hydroxyphenyl, 3, 5-diodo-2-hydroxyphenyl, pyrimidines) on their properties. Moreover, the properties in the aggregating state were tested in the MeOH/PBS system. Imines are susceptible to the hydrolysis process and aggregation-caused photoluminescence quenching (ACQ). In turn, β-ketoenamine shown excited-state intramolecular proton transfer promoted by aggregation (AIEE). Our studies can be helpful in the further design of compounds containing the 1, 8-naphthalimide structure for various applications. Graphical abstract: Image 1 Highlights: Properties of 1, 8-Naphthalimide derivatives with imine and β-ketoenamine bonds were compared. Thermal, electrochemical and optical investigation were preformed. The β-ketoenamine derivatives exhibited aggregation-induced emission (AIE). The analyzed derivatives were used in OLEDs and in cell imaging.